2020
DOI: 10.1149/1945-7111/ab679f
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Method to Prepare Ultrafine Pd Nanoparticles Embedded into N-Doped Porous Carbon Nanosheets as Highly Efficient Electrocatalysts for Oxygen Reduction Reaction

Abstract: To explore cheap alternatives for platinum electrocatalysts, many strategies have been widely studied. And Pd is regarded as a ideal alternative catalyst due to its high stability and catalytic activity. In this work, we designed a facile method to prepare a highly efficient electrocatalyst in which ultrafine Pd nanoparticles are embedded into N-doped porous carbon nanosheets for oxygen reduction reaction (ORR) in alkaline and acid media. A series of products with different Pd quantities were in situ prepared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
(46 reference statements)
1
6
0
Order By: Relevance
“…Porous carbon as support has several advantages compared to the traditional carbon black, such as larger surface area, confinement effect and accessible catalytic active sites. In recent years, a variety of porous carbons, such as porous carbon nanosheets, [269] 3D-graphene nanosheets (GNS), [270,271] ordered mesoporous carbon, [272] N-doped ordered mesoporous carbon nanospheres, [273] N-doped porous carbon nanosheets, [274] 3D porous N-doped carbon nanofiber, [275] and some organic frameworks derived porous carbons [178,256] have been explored as the support of Pd-based catalysts. For instance, Atanassov et al comparatively studied the ORR kinetics of Pd nanoparticles supported on 2D-GNS and 3D-GNS with micro and macro pores, respectively, and demonstrated that the porosity and pore size play important roles in enhancing the ORR performance and improving the O 2 mass transport in the high current density region.…”
Section: Liquid Cell Evaluation Of Pgm-based Electrocatalystsmentioning
confidence: 99%
“…Porous carbon as support has several advantages compared to the traditional carbon black, such as larger surface area, confinement effect and accessible catalytic active sites. In recent years, a variety of porous carbons, such as porous carbon nanosheets, [269] 3D-graphene nanosheets (GNS), [270,271] ordered mesoporous carbon, [272] N-doped ordered mesoporous carbon nanospheres, [273] N-doped porous carbon nanosheets, [274] 3D porous N-doped carbon nanofiber, [275] and some organic frameworks derived porous carbons [178,256] have been explored as the support of Pd-based catalysts. For instance, Atanassov et al comparatively studied the ORR kinetics of Pd nanoparticles supported on 2D-GNS and 3D-GNS with micro and macro pores, respectively, and demonstrated that the porosity and pore size play important roles in enhancing the ORR performance and improving the O 2 mass transport in the high current density region.…”
Section: Liquid Cell Evaluation Of Pgm-based Electrocatalystsmentioning
confidence: 99%
“…[25,53,59,60] For instance, N doping can modulate the electron-neutrality of neighboring carbon atoms and improve the adsorption of O 2 species. [61,62] As reported in previous studies, [21,29] DFT calculations showed that the reverse electronegativity between P and S can lead to a unique electron-donor property in S-phosphide and the synergistic coupling effect between P, S and carbon, which facilitates ORR electrocatalysis. [2,3] Last but not least, the presence of metallic cobalt as a conductive electrocatalytic material provided more active sites, and Co 2 P played a key role in optimizing the catalytic active site towards ORR, where charge transfer between P and Co led to activation of the encapsulated carbon shell, as observed previously.…”
Section: Resultsmentioning
confidence: 70%
“…The other additional peaks (orangecolored) observed around 342.7 and 335.8 eV are attributed to 3d regions of PdO. [27][28][29][30] To calculate the activation energy (Ea # ) of the Pd/Al 2 O 3 catalyst in the MB hydrolysis, the catalytic reaction was performed at different temperatures ranging from 298 to 328 K (Figure 5(a)). As can be seen from the figure, the rate of H 2 production gradually increases with increasing temperature, and the rate constant values obtained from the slope of each line from Figure 5(a) are graphed to obtain Arrhenius plot (Figure 5(b).…”
Section: Resultsmentioning
confidence: 99%